2003
DOI: 10.1056/nejmoa032290
|View full text |Cite|
|
Sign up to set email alerts
|

Single versus Double Autologous Stem-Cell Transplantation for Multiple Myeloma

Abstract: As compared with a single autologous stem-cell transplantation after high-dose chemotherapy, double transplantation improves overall survival among patients with myeloma, especially those who do not have a very good partial response after undergoing one transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
682
4
21

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 968 publications
(741 citation statements)
references
References 20 publications
(14 reference statements)
34
682
4
21
Order By: Relevance
“…Further, in a Spanish randomized trial, patients responding to induction therapy failed to benefit from ASCT trial, suggesting that the greatest benefit from early ASCT may be mainly among the small proportion of patients with disease refractory to induction therapy [92]. Two randomized trials have found benefit with tandem (double) versus single ASCT, with the benefit primarily seen in patients failing to achive CR or VGPR with the first ASCT [93,94]. Two other randomized trials, however, have yet to show significant improvement in OS with double ASCT [95,96].…”
Section: Role Of Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…Further, in a Spanish randomized trial, patients responding to induction therapy failed to benefit from ASCT trial, suggesting that the greatest benefit from early ASCT may be mainly among the small proportion of patients with disease refractory to induction therapy [92]. Two randomized trials have found benefit with tandem (double) versus single ASCT, with the benefit primarily seen in patients failing to achive CR or VGPR with the first ASCT [93,94]. Two other randomized trials, however, have yet to show significant improvement in OS with double ASCT [95,96].…”
Section: Role Of Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%
“…Most randomised trials comparing single with tandem ASCT have shown no benefit in overall survival from tandem stem cell transplantation (Attal et al, 2003;Fermand et al, 2005b;Cavo et al, 2007;Mai et al, 2016;Sonneveld et al, 2007; reviewed by Kumar et al, 2009). Many of these trials utilised non-standard conditioning regimens (e.g.…”
Section: Tandem Transplantsmentioning
confidence: 99%
“…Many of these trials utilised non-standard conditioning regimens (e.g. oral busulfan or TBI) which have since been shown to be inferior to standard mel200 (Attal et al, 2003;Fermand et al, 2005b;Cavo et al, 2007;Sonneveld et al, 2007). However the GMMG-HD2 trial, which used tandem standard mel200 ASCT, showed no difference in survival (Mai et al, 2016).…”
Section: Tandem Transplantsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include sequential HDCT [20,21] or more courses of HDCT [22], as reported for multiple myeloma [23]. Indeed, even in patients in complete remission after a single HDCT course, the assumption can be made that lymphoma cells are not detectable but still present, and are responsible for a subsequent relapse.…”
Section: Introductionmentioning
confidence: 99%